(untitled) (Interdisciplinary Studies Journal, 2024)
In this essay, we propose a reflection on the political impacts of what we term decolonial attitude artivisms. We engage in dialogue with authors associated with De(s)colonial Studies, as well as with the productions and performative creations of artivist individuals. These individuals do not merely serve as "objects of analysis," a common approach in many investigations, but rather as integral to our conceptual and theoretical framework. A central concept explored in the text is colonial echoes, which serves as a crucial lens for understanding the reverberations of the colonial project and the creative forms of cultural re(ex)resistance mobilized by the artivisms under discussion. The essay concludes by asserting that artivisms with a decolonial attitude represent creative insurgencies that serve as responses to the various forms of power governing life, particularly racism and heteronormativity.